Chasing Stars: Racial Tasking of Recruiting Responsibilities among Power-5 Football Coaches - Chris Corr; Trevor Bopp; Christopher Atwater; Calvin Nite (University of Kansas Libraries, 2023)
During the 2022 National Collegiate Athletic Association (NCAA) college football season, eight of the 65 Power-5 head coaches were Black. The racial composition of assistant coaches, however, was nearly 50% Black and 50% White. While the head coach of a Power-5 football team serves as the leader of the program, the 10 assistant coaches permitted by the NCAA oversee a variety of critical roles; the most valuable of which is recruiting. This study extends previous work by examining the racial composition of Power-5 football coaching staffs and recruiting responsibilities through the lens of racial tasking. An analysis of Power-5 football recruiting classes from 2019 and 2020 illustrates that assistant coaches are tasked with recruiting recruits racially similar to themselves 58% of the time. Furthermore, Black assistant coaches are disproportionately tasked with recruiting Black recruits and higher rated recruits (i.e., five- and four-star) compared to their White counterparts. We contend such racialized responsibilities and expectations may affect opportunities for advancement among Black assistant coaches.